Shape-memory responses compared between random and aligned electrospun fibrous mats - Wang, Xianliu; Zhang, Zhaowenbin; Qin, Chunping; Guo, Xuran; Zhang, Yanzhong (Frontiers in Bioengineering and Biotechnology, 2023)
Significant progress has been made in the design of smart fibers toward achieving improved efficacy in tissue regeneration. While electrospun fibers can be engineered with shape memory capability, both the fiber structure and applied shape-programming parameters are the determinants of final performance in applications. Herein, we report a comparison study on the shape memory responses compared between electrospun random and aligned fibers by varying the programming temperature Tprog and the deforming strain εdeform. A PLLA–PHBV (6:4 mass ratio) polymer blend was first electrospun into random and aligned fibrous mat forms; thereafter, the effects of applying specific Tprog (37°C and 46°C) and εdeform (30%, 50%, and 100%) on the morphological change, shape recovery efficiency, and switching temperature Tsw of the two types of fibrous structures were examined under stress-free condition, while the maximum recovery stress σmax was determined under constrained recovery condition. It was identified that the applied Tprog had less impact on fiber morphology, but increasing εdeform gave rise to attenuation in fiber diameters and bettering in fiber orientation, especially for random fibers. The efficiency of shape recovery was found to correlate with both the applied Tprog and εdeform, with the aligned fibers exhibiting relatively higher recovery ability than the random counterpart. Moreover, Tsw was found to be close to Tprog, thereby revealing a temperature memory effect in the PLLA–PHBV fibers, with the aligned fibers showing more proximity, while the σmax generated was εdeform-dependent and 2.1–3.4 folds stronger for the aligned one in comparison with the random counterpart. Overall, the aligned fibers generally demonstrated better shape memory properties, which can be attributed to the macroscopic structural orderliness and increased molecular orientation and crystallinity imparted during the shape-programming process. Finally, the feasibility of using the shape memory effect to enable a mechanoactive fibrous substrate for regulating osteogenic differentiation of stem cells was demonstrated with the use of aligned fibers.